Urban Gaming Simulation for Enhancing Disaster Resilience. A Social Learning Tool for Modern Disaster Risk Management - Promsaka Na Sakonnakron, Sarunwit; Huyakorn, Pongpisit; Rizzi, Paola (TeMA - Journal of Land Use, Mobility and Environment, 2014)
An emergence of the disaster resilience concept broadens the idea of urban risk management and, at the same time, enhances a theoretical aspect in a way in which we can develop our cities without making it more vulnerable to natural disasters. Nevertheless, this theoretical plausibility is hardly translated into a practical implication for urban planning, as the concept of resilience remain limited to some scholars’ debate. One of substantial factors that limit the understanding of people about disaster risk an resilience is a lack of risk awareness and risk preparedness, which can be solved by restructuring social learning process that enable a process of mutual learning between experts and the public. This study, therefore, focuses on providing insights into the difficulties of disaster risk communication we face, and how gaming simulation can be taken as a communication technique in enhancing social learning, which is regarded as a fundamental step of disaster risk management prior the mitigation process takes place. The study argues that the gaming simulation can facilitate planners in acquiring risk information from the community, conceiving the multitude of complex urban physical and socio-economic components, and conceptualizing innovative solutions to cope with disaster risks mutually with the public.